Electrochemical Oxidation Effect of Nicotine in Cigarette Tobacco on a Blood Medium Mediated by GCE Using Cyclic Voltammetry - Radhi,Muhammed Mizher (2020)
The electrochemical behaviour of nicotine extracted from commercial cigarette tobacco were studied in a blood media, at a glassy carbon electrode (GCE), using cyclic voltammetry technique. The nicotine compound oxidized the blood component in neutral media, at pH 7.4. The response was evaluated with respect to different pH values, scan rates, concentrations and temperatures. From the voltammogram of nicotine in a blood medium, it was found that the oxidation current peak of nicotine was +999 mV in acidic and alkaline media, which enhanced about twice in an acidic medium and disappeared in an alkaline medium. In its turn, at highly acidic media, three reduction current peaks appeared in the nicotine voltammogram in blood media. The electrochemical behavior of nicotine was investigated using cyclic voltammetry technique; the method was successfully applied for the determination of the nicotine compound which had a reversible redox couple in a blood medium from the peak potential separation of 100 mV. Also, it was found that the average value of the diffusion coefficient at the cathodic electrode was 4.075x10(11) cm-2 s-1, and 22.625x10(11) cm-2 s-1 at the anodic electrode.